Wellness: A holistic understanding of its pursuit, perceptions and wellbeing motives according to young adults - Afonso, Veronica Neves (2022)
Health and wellness are valuable to the marketplace and have long-been reduced to solutions that focus on physical activity or diet. In recent years, the rise to more integrated means of wellness has flourished, with app-enabled solutions encouraging consumers proactive pursuit of their own health and wellbeing. When looking into wellness and its history, it is evident that wellness is a holistic construct in which various pillars of health must be satisfied. This highlights pillars such as environment, spirituality and social wellbeing which seem to often be neglected in the health and wellness space. When reflecting on marketing literature around wellness, a holistic outlook is also neglected. Moreover, the opportunity to explore meanings and motivations consumers ascribe to wellness pursuit is additionally overlooked. This interview-based interpretive analysis delves into young-adults’ perceptions around wellness, namely, what wellness means to them, how they self-direct their wellness and whether wellness is perceived holistically by them. In order to understand meanings, a theoretical framework around hedonic and eudemonic wellbeing is called upon, to better understand the orientations and motivations that these young adults obtain. Hedonia pertains to a wellbeing derived from the increase of positive mood, a pleasure derived state. Differently, eudemonia relates to a wellbeing focused on living in accordance with your truest sense of self and living life to its fullest potential. Findings indicate that both hedonic and eudemonic wellbeing are encouraging and rewarding motives to the young adults in this study. Lending to wellness being reliant on self-directed behaviour, solutions in the health and wellness space that adhere to both wellbeing attributes, rather than solely hedonic properties, could perhaps secure and motivate a more consistent behaviour maintenance by satisfying a more all-encompassing state of wellbeing. Further findings from this study illuminate that these young adults view wellness as holistic and multidimensional. Important is this emphasis on individuals, there lies a unique property to wellness. While one pillar of health may be more central to one’s life, another may be more critical for someone else. Such underpins how health and wellness solutions in the marketplace should adhere to this, by offering more holistic solutions to better support different health pillars, particularly spirituality which illuminated itself as a critical source of eudemonic wellbeing. By means of this, solutions in the marketing space can better support young adults’ attainment of wellbeing who considerably suffer with mental health issues.